Rethinking Community Corrections - Brusman Lovins, Lori (Victims & offenders, 2021)
Over the past four decades, the field of community corrections has evolved considerably. The “tough on crime” movement of the 1980s propelled an increase across the board in justice-involved populations, one that has seen a slow descent in the last 13 years. This essay will trace the work of Edward J. Latessa – a scholar whose work helped redefine the field of community corrections. Ed’s mission has been to help agencies apply scientific knowledge to everyday practices by operationalizing the principles of effective intervention into practical strategies agencies can employ. He has accomplished this by producing work that has been pragmatic, evolving, and accessible to practitioners and policymakers. This essay explores the mechanisms Ed has used to help change the field of community corrections from one focused on monitoring and sanctioning, to using research-supported rehabilitative practices.